Letter - Winstanley, E.
030-0017-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. OUR REFERENCE EXPORT 1733 ST/HP. YOUR REFERENCE 21st October, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON SW.1 Dear Sirs, We beg to make further reference to your order of the 15th instant, in respect of goods for shipment to Spain. It was originally intended that our s.s. NEW PIONEER would sail from Garston on Wednesday, the 26th instant, for Rouen, but unfortunately the vessel in question is at present out of commission, and consequently, shipment will have to be deferred until November 2nd, when our s.s. "C.W.S. PROGRESS" will be leaving Garston for Rouen. We hope the above will not occasion any serious inconvenience, and meanwhile, remain, Yours faithfully, E. Winstanley Export Department. 292/946/30/17